Hunting in early Stuart England: status, sociability, and politics - Rose, Tom (2020)
This thesis explores the importance of hunting in early Stuart England: its use in the construction of gentry and noble status and identity, the sociability that resulted from participation in the sport, and the political significance of such sociable behaviour. The first chapter will suggest that hunting was a prominent way in which elite identity was displayed during this period, but also that the sport was subject to multiple tensions generated by social mobility, competition amongst the gentry for honour and status, the changing role of gentry and noble elites during this period, and the rise of puritanism. The second chapter further investigates how hunting was an exclusive pastime by examining what was needed to put on a hunt. An analysis of the different styles of hunting practised demonstrates that the sport was an extremely flexible form of elite sociability and one which reflected the changing nature of elite lifestyles.